Fred Taylor : brother in the shadows - Virtue, John (McGill-Queen's University Press, 2008)
John Virtue uncovers the dynamics of a prominent Ottawa family and reveals the divergent paths of brothers E.P. and Fred Taylor. E.P. became mid-century Canada's leading industrialist, while Fred became an artist and a Communist.